Clinico-aetiological profile and outcome patterns of neonatal seizures at a tertiary care centre - Agrawal, Vijay; Bagri, Dhan Raj; Sharma, J. N.; Singh, Roop (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal seizures are a major risk factor for neonatal mortality and subsequent neurological disability. The incidence of seizure varies from 1.5-3.7/1000 live birth; while in NICU it can be up to 5/1000 live birth. Methods: This Descriptive type of observational study aimed to study clinical profile, aetiology in neonatal seizures and short term outcome was done in all Neonatal units attached to paediatric Department of SMS Medical College, Jaipur. Results: In the 100 cases Majority of neonates had onset of seizure <3 days (<72 hours) 53% and remaining 47% neonates had onset of seizure >3 days (>72 hours). Most common type of neonatal seizure was subtle(75%), other types were tonic seizure (17.3%), clonic seizure (5.1%) and least common type was myoclonic (2.5%). Most common cause of neonates seizure noted was birth asphyxia (73%) second common cause is pyomeningitis and third common cause is hypoglycaemia. Most common cause of neonatal seizure both in full term (71.17%) and preterm (25%) is birth asphyxia. Second most common cause of neonatal seizure in full term is pyomeningitis (8.70%) and in preterm is pyomeningitis and hypoglycaemia (25%). Most common cause of neonatal seizure both in onset of seizure <3 days (<72 hours) 53% and in onset of seizure >3 days (>72 hours). Conclusions: Out of total 100 cases, neonates with normal birth weight 92% and low birth weight 8%. Majority of neonates had onset of seizure <3 days (<72 hours) 53% and remaining 47% neonates had onset of seizure >3 days (>72 hours). Majority of neonates with seizure delivered by vaginal route (86%) and remaining 14% neonates were delivered by LSCS.